2021
DOI: 10.1186/s12864-021-08195-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteins associated with bast fiber growth of ramie by differential proteomic analysis

Abstract: Background Ramie is an important fiber-producing crop in China, and its fibers are widely used as textile materials. Fibers contain specialized secondary cellular walls that are mainly composed of cellulose, hemicelluloses, and lignin. Understanding the mechanism underlying the secondary wall biosynthesis of fibers will benefit the improvement of fiber yield and quality in ramie. Results Here, we performed a proteomic analysis of the bark from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…Numerous efforts have been made to determine the fiber growth mechanism [ 21 , 27 , 29 , 30 ], which has greatly improved our understanding of its genetic regulation and lead to the establishment of a putative model for fiber formation [ 28 ]. Protein post-translational modifications, such as phosphorylation and ubiquitination, are involved in fiber formation [ 35 , 37 ], indicating a complex mechanism involved in fiber growth. Although differentially expressed miRNAs and circular RNAs have been identified in the stem bark of growing fibers in ramie [ 20 , 37 ], the specific roles of these ncRNAs and their targets remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous efforts have been made to determine the fiber growth mechanism [ 21 , 27 , 29 , 30 ], which has greatly improved our understanding of its genetic regulation and lead to the establishment of a putative model for fiber formation [ 28 ]. Protein post-translational modifications, such as phosphorylation and ubiquitination, are involved in fiber formation [ 35 , 37 ], indicating a complex mechanism involved in fiber growth. Although differentially expressed miRNAs and circular RNAs have been identified in the stem bark of growing fibers in ramie [ 20 , 37 ], the specific roles of these ncRNAs and their targets remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in cell wall structure and components were another important factor affecting cell elongation (Scheible and Pauly, 2004 ; Coomey et al, 2021 ; Li et al, 2021 ; Wang et al, 2021 ). In Shidu bamboo, corresponding signs, such as the thinning of its fiber cell wall and the decrease in lignin, cellulose, and hemicellulose content in the culm wall compared with the prototype plant ( Table 1 ; Figures 5B–D ), indicate that its cell wall exhibits abnormal development.…”
Section: Discussionmentioning
confidence: 99%
“…Three genes, Bnt03G004997, Bnt06G010588, and Bnt03G004081, showed relatively high expression level in the stems of ZSZ1, but in tenacissima, they mainly expressed in the leaves, indicating a difference in the expression pattern of them. Furthermore, the expression level of these 10 NAC genes were compared between the barks from the top and middle section of the stems where fiber growth is under different stages [39], and revealed that the transcript abundance of eight genes had a more than two-fold difference (Figure 2d), indicating the potential roles of these NAC regulators in the fiber growth of ramie. We further focused on the expression of NAC genes encoding the ortholog of the Arabidopsis secondary wall biosynthetic NAC regulator.…”
Section: Expression Analysis Of Ramie Nac Genesmentioning
confidence: 99%